Perlawanan Hegemoni Kekuasaan dalam Puisi Diponegoro, Aku Tulis Pamflet Ini, Kita Pemilik Sah Republik Ini, Perlawanan, Teratai - Oematan, Ricard; Fallo, John Darwis; Isu, Rudolf J. (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2022)
This research is about the resistance to the hegemony of power in poetry. The problem that is realized is how to fight the hegemony of power in the five Indonesian poems. Based on the research problem formulated, the research objective is to interpret the resistance to the hegemony of power in the five Indonesian poets. The method used is an interpretive qualitative research method, using a hegemonic approach as its approach. In the research on the resistance to the hegemony of power in poetry, â€œDiponegoroâ€ by: Chairil Anwar, â€œAku Tulis Pamflet Iniâ€ by: W. S. Rendra, â€œKita Pemilik Sah Republik Iniâ€ by: Taufiq Imail, â€œPerlawananâ€ by: Mansur Samin, dan â€œTerataiâ€ by: Sanoesi Pane as the five Indonesian poems used as data in the study.